The Influence of the Application of Video Media on Learning Activities and Science Learning Outcomes for Grade 6 Elementary School Students: Pengaruh Penerapan Media Video terhadap Aktivitas Belajar dan Hasil Belajar IPA Siswa Kelas 6 Sekolah Dasar - Karimah, Inayatul; Arifin, Moch. Bahak Udin By (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of the application of video media on learning activities and science learning outcomes for fourth grade students of MINU Kedungcangkring. The research method used is quantitative with a causal comparative research design which is tested in one class. The assessment instrument used is a statement in the form of multiple choice, totaling 10 questions to find out the answers of the respondents. The sample of this study was class IV at MINU Kedungcangkring with a total of 25 students. The sampling technique in this research is sampling. Data analysis used Anova simple linear regression test. Data analysis used a simple linear regression test through the IBM SPSS 24.0 application. The results of the study on the linear regression test of video media on learning activities showed that the significance value of 0.000 was smaller than the significant level of 0.05, on video media on learning outcomes of 0.285 and on learning activities on learning outcomes it had a value of 0.641 where the overall value was significant. > the significant level used is 0.05. Based on the results of this study, it can be concluded that there is an effect on the application of video media to learning activities but does not affect learning outcomes, learning activities and learning outcomes.